Agile Software Quality of Adaptability Risk Measurement using Fuzzy Inference System - Rai, Anand Kumar; Agrawal, Shalini; Khaliq, Mazahar (International Journal of Computer Sciences and Engineering, 2025)
Quality of agile software is one of the major issues in software vigorous systems, and it is important to examine methodically it as early as possible. An increasingly important quality attribute of complicated software systems is adaptability. Agile software development methodologies are very useful since their beginning to improve the quality of the software product. In this paper an innovative practice has been presented for evaluating agile software quality of adaptation using the Fuzzy Inference System in order to determine the developed software quality acceptance degree.